Chronic liver disease in homeless individuals and performance of non‐invasive liver fibrosis and injury markers: VALID study. (10th December 2021) - Hashim, Ahmed.; Bremner, Stephen; Grove, Jane I.; Astbury, Stuart; Mengozzi, Manuela; O'Sullivan, Margaret; Macken, Lucia; Worthley, Tim; Katarey, Dev; Aithal, Guruprasad P.; Verma, Sumita
Abstract: Background/aims: Community‐based assessment and management of chronic liver disease (CLD) in people who are homeless (PWAH) remain poorly described. We aimed to determine prevalence/predictors of CLD in PWAH and assess the performance of non‐invasive liver fibrosis and injury markers. Methods: The V ulnerable A dult LI ver D isease (VALID) study provided a "one‐stop" liver service based at homeless hostels. Our primary outcome was the prevalence of clinically significant hepatic fibrosis (CSHF; liver stiffness measurement (LSM) ≥8 kPa). Results: Total individuals recruited were 127, mean ± SD age 47 ± 9.4 years, 50% (95% CI 41%‐59%) and 39% (95% CI 31%‐48%) having alcohol dependence and a positive HCV RNA respectively. CSHF was detected in 26% (95% CI 17%‐35%), independent predictors being total alcohol unit/week (OR 1.01, 95% CI 1.00‐1.02, P  = .002) and HCV RNA positivity (OR 2.93, 95% CI 1.12‐7.66, P  = .029). There was moderate agreement between LSM and Enhanced Liver Fibrosis (ELF) score (kappa 0.536, P  < .001) for CSHF as assessed by LSM ≥8 kPa. Those with CSHF had significantly higher levels of IFN‐γ ( P  = .002), IL‐6 ( P  = .001), MMP‐2 ( P  = .006), ccCK‐18 ( P  < .001) and ELF biomarkers ( P  < .001), compared to those without CSHF. Service uptake was ≥95%. Direct acting antiviral (DAA) treatment completion was 93% (95% CI 77%‐99%), sustained virological response (SVR) being 83% (95% CI 64%‐94%). Conclusion: There is a significant liver disease burden from HCV and alcohol in PWAH. Non‐invasive liver fibrosis and injury markers can help in identifying such individuals in the community. Despite a challenging cohort, excellent service uptake and high DAA‐based SVRs can be achieved.